The anti-obesity effects of polyphenols: a comprehensive review of molecular mechanisms and signal pathways in regulating adipocytes - He, Lan; Su, Zhan; Wang, Shuangshuang (Frontiers in Nutrition, 2024)
Excess weight gain is a growing concern worldwide, fueled by increased consumption of calorie-dense foods and more sedentary lifestyles. Obesity in China is also becoming increasingly problematic, developing into a major public health concern. Obesity not only increases the risk of associated disease but also imposes a burden on health care systems, and it is thus imperative that an effective intervention approach be identified. Recent studies have demonstrated that the polyphenol-rich Mediterranean diet has considerable potential in this regard. Polyphenols can inhibit the production of adipocytes and reduce adverse reactions, such as inflammation, insulin resistance, and gut microflora imbalance. In this review, we examine four polyphenols (curcumin, ellagic acid, ferulic acid and quercetin) in terms of their potential as interventions targeting obesity.The mechanisms that help promote adipocyte browning, increase thermogenic factors, increase thermogenesis, and regulate adipocyte differentiation are summarized, and key signaling pathways, including PPARγ, C/EBP-, and others, are reviewed.